Performance and neuromuscular adaptations following differing ratios of concurrent strength and endurance training - Jones, T. W.; Howatson, G.; Russell, M.; French, D. N. (The Journal of Strength and Conditioning Research, 2013)
The interference effect attenuates strength and hypertrophic responses when strength and endurance training are conducted concurrently; however, the influence of training frequency on these responses remain unclear when varying ratios of concurrent strength and endurance training are performed. Therefore, the purpose of the study was to examine the strength, limb girth, and neuromuscular adaptations to varying ratios of concurrent strength and endurance training. Twenty-four men with >2 years resistance training experience completed 6 weeks of 3 days per week of (a) strength training (ST), (b) concurrent strength and endurance training ratio 3:1 (CT3), (c) concurrent strength and endurance training ratio 1:1 (CT1), or (d) no training (CON) in an isolated limb model. Assessments of maximal voluntary contraction by means of isokinetic dynamometry leg extensions (maximum voluntary suppression [MVC]), limb girth, and neuromuscular responses through electromyography (EMG) were conducted at baseline, mid-intervention, and postintervention. After training, ST and CT3 conditions elicited greater MVC increases than CT1 and CON conditions (p ? 0.05). Strength training resulted in significantly greater increases in limb girth than both CT1 and CON conditions (p = 0.05 and 0.004, respectively). The CT3 induced significantly greater limb girth adaptations than CON condition (p = 0.04). No effect of time or intervention was observed for EMG (p > 0.05). In conclusion, greater frequencies of endurance training performed increased the magnitude of the interference response on strength and limb girth responses after 6 weeks of 3 days a week of training. Therefore, the frequency of endurance training should remain low if the primary focus of the training intervention is strength and hypertrophy.